Game Online dan Dampaknya di Mahasiswa - M. Maulana Mas’udi (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTIn this globalization era, developments in the field of communication are very fast and sophisticated, everything is easily obtained. The development of games in big cities in Indonesia is very rapid, it is marked by the proliferation of game canters that offer many facilities to play multiplayer games both local (LAN) and online types of games such as these are called online multiplayer games or commonly referred to as call with online games that involve many games at once to interact with one another at the same time.Games began to be regarded as something addicted (opium), gamers were able to sit for long for the sake of the game and survive there without wanting a disturbance that could break its concentration in playing the online game.In this research the researcher uses a qualitative descriptive analysis method. Before the data is analyzed, there are several steps that must be taken in managing data. This research uses qualitative research. This research aims to provide an overview and research problems in the field in order to realize the basic information regarding the background or context of a social phenomenon that exists in adolescents.The students who became gamers on average claimed to be gamers because they were invited by their friends who had previously struggled in this hobby. Indeed the factor of wanting to look for relieving fatigue and entertainment is also one of the drivers for them to try out the world of online gaming.Online games have a negative impact on gamers, but there are also positive effects of online gaming. The positive impact will arise if teenagers can play online games on time i.e playing online games regularly, not doing every day and not doing even for hours.Islam is actually a religion that respects the objective reality and the concrete reality that is found around and within humans (al-Islam din wâqi’iy). When humans like splendor, beauty, good looks, delicacy and independence, Islam then justifies it (al-Nahl: 6, al-A'raf: 31), provided that it is obtained in a good way and done in the right way (al- Baqarah: 42).Keywords: Impact of Online Games, Religious Intensity